Evaluating restoration trajectories using DNA metabarcoding of ground‐dwelling and airborne invertebrates and associated plant communities. Issue 7 (17th February 2022) - van der Heyde, Mieke; Bunce, Michael; Dixon, Kingsley W.; Fernandes, Kristen; Majer, Jonathan; Wardell‐Johnson, Grant; White, Nicole E.; Nevill, Paul
Abstract: Invertebrates are important for restoration processes as they are key drivers of many landscape‐scale ecosystem functions; including pollination, nutrient cycling and soil formation. However, invertebrates are often overlooked in restoration monitoring because they are highly diverse, poorly described, and time‐consuming to survey, and require increasingly scarce taxonomic expertise to enable identification. DNA metabarcoding is a relatively new tool for rapid survey that is able to address some of these concerns, and provide information about the taxa with which invertebrates are interacting via food webs and habitat. Here, we evaluate how invertebrate communities may be used to determine ecosystem trajectories during restoration. We collected ground‐dwelling and airborne invertebrates across chronosequences of mine‐site restoration in three ecologically disparate locations in Western Australia and identified invertebrate and plant communities using DNA metabarcoding. Ground‐dwelling invertebrates showed the clearest restoration signals, with communities becoming more similar to reference communities over time. These patterns were weaker in airborne invertebrates, which have higher dispersal abilities and therefore less local fidelity to environmental conditions. Although we detected directional changes in community composition indicative of invertebrate recovery, patterns observed were inconsistent between study locations. The inclusion of plant assays allowed identification of plant species, as well as potential food sources and habitat. We demonstrate that DNA metabarcoding of invertebrate communities can be used to evaluate restoration trajectories. Testing and incorporating new monitoring techniques such as DNA metabarcoding is critical to improving restoration outcomes.